Theatre, Performance and Change (Springer International Publishing, 2018)
This book works to 'make change strange' from and for the field of theatre and performance studies. Growing from the idea that change is an under-interrogated category that over-determines theatre and performance as an artistic, social, educational, and material practice, the scholars and practitioners gathered here (including specialists in theatre history and literature, educational theatre, youth arts, arts policy, socially invested theatre, and activist performance) take up the question of change in thirty-five short essays. For anyone who has wondered about the relationships between theatre, performance and change itself, this book is an essential conversation starter.